Common components of home-based family therapy models: the HBFT partnership in Kansas - Macchi, C.R.; O'Conner, Nancy (My University, 2010)
In this article, we provide an analysis of components shared by varying home-based family therapy (HBFT) practices and evidence-based models. Applying a consistent statewide standard for HBFT presents challenges for the training of therapists from varying disciplines, with different levels of experience, and from diverse agencies. We propose focusing on common components across existing evidence-based models and discuss the trainings developed to integrate those components. We address indications and contraindications for using an HBFT approach and illustrate ways to address the particular challenges of HBFT supported by a unique partnership in Kansas. We conclude by offering suggestions for further research and for continued training development.
Keywords: Home-based family therapy; Training; Evidence-based practice